Diagnosing the service quality improvement of university libraries in intuitionistic fuzzy environment - Tooranloo, Hossein Sayyadi; Ayatollah, Arezoo Sadat; Marvasti, Mahtab Tavangar (Malaysian Journal of Library and Information Science, 2018)
Libraries and information centres are service organizations connecting academic communities to knowledge and information through efficient services as their main mission. Given the importance of high-quality services in libraries and increased users’ demand for receiving better service, the promotion of service quality levels is as one of the crucial challenges of libraries. This study is an attempt to provide a model for diagnosis of library service quality using Failure Modes and Effects Analysis (FMEA) approach in an intuitionistic fuzzy environment. The proposed model is applied in libraries of Yazd University of Science and Art in Iran. Accordingly, 25 failure items of library service quality in library services are first determined for diagnosis through reviewing the literature and interviewing the academic experts, as well as library managers at Yazd University of Science and Art. Following the determination of these items, a questionnaire was administered to the experts. The results indicate that "the lack of appropriate social spaces for group learning and study" is an item of highest priority in quality improvement of library service. The results of this research can be used to guide managers and decision makers in order to plan for improving the quality of library services.